On the Scope of GaN-Based Avalanche Photodiodes for Various Ultraviolet-Based Applications - Ji, Dong; Chowdhury, Srabanti (Frontiers in Materials, 2022)
We present a review of GaN avalanche photodiodes. GaN-based avalanche photodiodes are of emerging interest to the device community. The review covers various important aspects of the device such as the design space, substrate choice, edge termination efficacy, and last, but not least, the physics behind the avalanche breakdown in GaN. The study comprehends the reported impact ionization coefficients and how they may affect the device performances. Finally various reported GaN APDs are summarized and compared. We conclude that hole-initiated GaN APDs on free-standing GaN substrates can offer unprecedented advantages as UV light detectors, due to their ultra-high responsivity and low dark current.